"To be, or not to be": experiencing deterioration among people with young-onset dementia living alone. Issue 1 (1st January 2018) - Johannessen, Aud; Engedal, Knut; Haugen, Per Kristian; Dourado, Marcia Cristina Nascimento; Thorsen, Kirsten
ABSTRACT: Having dementia before the age of 65 (YOD) represents a radical break from an age-normative and expected life course. The disease afflicts the person's identity, threatens the self-image and self-confidence, and erodes the person's plans. The aim of the study was toexamine how people living alone with YOD perceive the course of dementia, their needs, and coping strategies, with a focus on narrating everyday life experiences. A longitudinal study using a qualitative approach was used. Five interviews, each with 10 informants, took place every 6 months from 2014 to 2017. The main theme is the person's experiences of changes of identity over time. The most significant aspects of their experiences of the dementia affecting them and their reactions are these: the initial signs, coping efforts, concealing the diagnosis, social retraction, existential anxiety, revival of the self, worse and worse, and health personnel as background. The study concluded thatpeople with dementia are able to describe their experiences and needs for a long time during the progression of dementia. Their voices should be listened to for planning of services. Personalized care should be used to support them in order to preserve their identity in a normalized everyday life as far as possible.